Utilization of expressed emotion in prevention of relapse of schizophrenia patients in Kelantan - M. Zain, Azhar; Varma, S.L. (1999)
Expressed emotion is currently among the most thoroughly investigated psychosocial research constructs in psychiatry (1-4).Developed some three decades ago by George Brown and his colleagues index of particular emotions, attitudes and behaviours expressed by relatives about a family member diagnosed with schizophrenia. The specific factors that make up the construct of expressed emotion are criticism, hostility and emotional over involvement.Several naturalistic studies have demonstrated the association of these factors with clinical relapse (5-8).Patients living in home are significantly more likely to experience a clinical relapse than are patients residing in households with low levels of expressed emotion.This finding has not surprisingly resulted in a great deal of clinical interest in a construct originally developed for purposes of basic research (9-12).